Development of Refractoriness of HO‐1 Induction to a Second Treatment with UVA Radiation and the Involvement of Nrf2 in Human Skin Fibroblasts. (27th October 2014) - Zhong, Julia Li; Raval, Chintan M.; Nisar, Muhammad Farrukh; Bian, ChunXiang; Zhang, Jin; Yang, Li; Tyrrell, Rex M.
Abstract UVA treatment of cultured human skin fibroblasts (FEK4) has been shown previously to reduce transcriptional activation of heme oxygenase 1 (HO‐1) following a second dose of UVA radiation, a phenomenon known as refractoriness. This study demonstrates that the levels of HO‐1 protein are also reduced after a second dose of UVA radiation as are Nrf2 levels, and there is less accumulation of Nrf2 in the nucleus where as Bach1 does accumulate in the nucleus. Cell viability is further reduced and cell membrane damage increased as compared with a single UVA treatment when an initial UVA treatment was followed by a second dose. Knockdown of Nrf2 by siRNA (siNrf2) targeting caused additional refractoriness of HO‐1 protein induction to a second UVA or heme treatment and this treatment also further enhanced cell damage by a second dose of UVA radiation. However, transfection with Nrf2 caused less refractoriness of HO‐1 to a second dose of UVA and reduced cell damage by a second dose of UVA radiation. These findings are consistent with the proposal that Nrf2 is involved in HO‐1 refractoriness and could serve as a cytoprotective factor against cell damage caused by repeated exposure to moderate doses of UVA radiation. We propose that protection by the Nrf2‐HO‐1 pathway protection may have clinical relevance since human skin is exposed repeatedly to UVA radiation.